Integrating Accounting and Non-Accounting Information Values and Their Impact on Decision-Making: A Case Study at Al-Mowasat Private Hospital - Abdulrazzaq, Huda Qahtan; Al-Tamimi, Suhail (NIU Journal of Management Sciences, 2026)
With the increasing demands of the healthcare sector, the need for integrated and valuable accounting and non-accounting information has become essential to supporting decision-makers and improving decision-making outcomes. Value integration of information is a modern approach that contributes to providing more relevant and reliable information, thereby enhancing the efficiency of decision-making processes within healthcare institutions. This study aimed to demonstrate the impact of value integration of accounting and non-accounting information on decision quality. It did so by integrating a decision analysis framework, specifically the Expected Value of Complete Information (EVPI) and Expected Value of Partial Information (EVSI), to measure the value of information and analyze its role in supporting decisions within the healthcare sector. The study employed a descriptive-analytical methodology, using a case study at Al-Mowasat Private Hospital. Data was collected through direct interviews with managers and the accountant, examination of official records and documents, content analysis, and the utilization of relevant data and reports to achieve the study's objectives. The results indicated that value integration of accounting and non-accounting information contributes to improving decision quality by reducing the error rate in decision-making. Keywords: Value integration of information, Decision-making.